Tree Diversity and Damage by Cypress Aphid, Cinara cupressi, on Juniperus procera in Gulele Botanical Garden and Entoto - Sitotaw Kebede; Tewodros Mulugeta (International Journal of Forestry Research)
Juniperus procera is an important tree species in Ethiopia. Increasing demand for fuelwood and construction material has also created markets for J. procera products. The impact of cypress aphid, Cinara cupressi, on J. procera is becoming catastrophic in the country. However, the level of cypress aphid damage on J. procera has never been studied in Entoto Mountain forest and Gullele Botanical Garden (GBG) in Ethiopia. The objective of this study was to assess the cypress aphid densities and extent of damage caused by the cypress aphid on solely and mixed planted J. procera in Entoto Mountain forest and GBG in Addis Ababa, Ethiopia, by evaluating aphid adult and nymph densities and damage to J. procera trees. Eight plots of 50 m∗50 m planted with pure J. procera and mixed J. procerawere selected at each site. Five 5 m∗5 m subplots were formed. To assess aphid density hthree tree twigs per whorl were sampled from each tree in the subplots randomly. The collected samples were examined in the laboratory for the presence of nymph and adult cypress aphid. Tree damage was assessed by visually observing the percentage of infestation in the tree crown and was scored on a 1–5 scale. The results showed significant differences in aphid densities between the sites. The highest aphid count was observed at Entoto Mountain. Besides, the solely planted J. procera trees had higher cypress aphid numbers than the mixed plantation. The mean percentage of aphid-infested trees in Entoto and GBG was 53.6 and 46.4, respectively. Tree mortality was extremely low in both sites and planting systems. The level of aphid damage was also significantly different between the planting systems, where mixed plantations had a lower aphid infestation level. Tree damage was directly correlated with the density of aphids collected. In conclusion, cypress aphid was apparent in both sites, and most of the trees were infested by this pest. However, the extent of damage varied with the planting system. Therefore, it is recommended to consider a mixed plantation of trees as one of cypress aphid management tools in J. procera.